1991
DOI: 10.1016/s0022-5347(17)37720-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prediction of Pathological Tumor Volume and Stage in Clinically Localized Prostate Cancer: Comparison of Digital Rectal Examination, Transrectal Ultrasonography and Magnetic Resonance Imaging

Abstract: Accurate preoperative staging is important for proper selection of patients for radical retropubic prostatectomy. Preoperative staging by digital rectal examination, transrectal ultrasound, magnetic resonance imaging (MRI), Gleason grade and prostate specific antigen was compared to pathological stage for 25 patients who underwent radical retropubic prostatectomy. The predictive value for tumor confinement was 36% by rectal examination, 37% by ultrasound and 30% by MRI. The predictive value for extracapsular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 43 publications
0
31
0
2
Order By: Relevance
“…It was confirmed that tu mors located ventrally and centrally in histopathologic specimens were Tumor volume is a predictor of pathologic stage (22). Except for one study performed with an externalarray coil (23), studies performed with endorectal coil (13) and body coil MR imaging (24)(25)(26)(27) reported a poor cor relation between MR tumor volume and the volume as calculated from the pathologic specimen. Mirowitz et al (6) who studied postcontrast Tlweighted images also reported poor correlation between the estimated and calculated volume.…”
Section: Discussionmentioning
confidence: 87%
“…It was confirmed that tu mors located ventrally and centrally in histopathologic specimens were Tumor volume is a predictor of pathologic stage (22). Except for one study performed with an externalarray coil (23), studies performed with endorectal coil (13) and body coil MR imaging (24)(25)(26)(27) reported a poor cor relation between MR tumor volume and the volume as calculated from the pathologic specimen. Mirowitz et al (6) who studied postcontrast Tlweighted images also reported poor correlation between the estimated and calculated volume.…”
Section: Discussionmentioning
confidence: 87%
“…When tumor volume is smaller than 4 cc metastasis is highly unlikely, whereas when tumor volume exceeds 12 cc metastasis is highly likely [20]. MR sequences with standard body coil and conventional spinecho techniques have not given accurate images for estimating tumor volume before surgery [5,[21][22][23][24][25]. However, fast spin-echo MR images obtained with a phased-array coil estimated tumor volume better [8].…”
Section: Objectivementioning
confidence: 99%
“…However, 20–50% of patients operated on for clinical T1–T2 tumors show extraprostatic spread at pathological examination. Current clinical methods used preoperatively to predict the extent of disease are still of limited value for a given patient [1, 2, 3]. Biopsy features have been extensively studied for this purpose and the usefulness of some of these characteristics (number of positive biopsy cores, length of invaded tissue within biopsy cores) has been clearly confirmed [4, 5, 6].…”
Section: Introductionmentioning
confidence: 99%